Applied mathematics in engineering and computer science - West, Frank (Willford Press, 2016)
As a branch of mathematics, applied mathematics has applications in a variety of disciplines ranging from science and engineering to business and economics. This innovative and comprehensive book integrates the well-developed theory and practical applications of applied mathematics especially in the fields of engineering and computer science. Differential equations, algebra, computational mathematics, etc. are some of the areas that have been elucidated in the text. It includes contributions of experts and scientists which will provide innovative insights into this field and will be extremely beneficial for research scholars.